A comparative study of feeding three sources of yeast on performance of broiler chicks - Daramola, S.T.; Bawa, G.S; Omage, J.J (Nigerian Journal of Animal Science, 2023)
Proximate analysis and biological studies were conducted to evaluate the performance of broiler chickens fed diets containing three sources of yeast. Brewer`s yeast slurry, local alcoholic yeast (BKT) and Bakers’ yeast were assayed for their proximate composition, metabolizable energy, calcium and phosphorus contents. Generally, the proximate composition of Dried brewer`s yeast slurry was similar to that of baker`s yeast but was slightly higher (P< 0.05) than local alcoholic yeast (BKT). Baker`s yeast contained more calcium and phosphorus (3.42 % and 4.34 %) than dried brewer`s yeast slurry (0.16% and 1.24%) and Burukutu yeast (0.08 % and 0.26 %). In the starter phase, a total of one hundred and ninety two – day old broiler chicks were used to compare the nutritive value of dried brewer`s yeast slurry , Burukutu (BKT) yeast and Baker`s yeast in a complete randomized design. The birds were fed 23 % CP diets in which yeast products were fixed at 0.8 %, while the control diet contained 0 % yeast which was fed throughout the 28 day’s experimental period. The growth trial showed no significant (P>0.05) difference across the dietary treatments in terms of final weight, feed intake, feed conversion ratio, protein efficiency ratio and the cost per Kg gain. It was concluded that in view of the high protein and fairly balanced amino acid profile of yeast products, yeast can be used as a growth promoter in broiler chickens diets.